Screening protocols to monitor respiratory status in primary immunodeficiency disease: findings from a European survey and subclinical infection working group. (25th August 2017) - Jolles, S.; Sánchez‐Ramón, S.; Quinti, I.; Soler‐Palacín, P.; Agostini, C.; Florkin, B.; Couderc, L.‐J.; Brodszki, N.; Jones, A.; Longhurst, H.; Warnatz, K.; Haerynck, F.; et al.
Summary: Many patients with primary immunodeficiency (PID) who have antibody deficiency develop progressive lung disease due to underlying subclinical infection and inflammation. To understand how these patients are monitored we conducted a retrospective survey based on patient records of 13 PID centres across Europe, regarding the care of 1061 adult and 178 paediatric patients with PID on immunoglobulin (Ig) G replacement. The most common diagnosis was common variable immunodeficiency in adults (75%) and hypogammaglobulinaemia in children (39%). The frequency of clinic visits varied both within and between centres: every 1–12 months for adult patients and every 3–6 months for paediatric patients. Patients diagnosed with lung diseases were more likely to receive pharmaceutical therapies and received a wider range of therapies than patients without lung disease. Variation existed between centres in the frequency with which some clinical and laboratory monitoring tests are performed, including exercise tests, laboratory testing for IgG subclass levels and specific antibodies, and lung function tests such as spirometry. Some tests were carried out more frequently in adults than in children, probably due to difficulties conducting these tests in younger children. The percentage of patients seen regularly by a chest physician, or who had microbiology tests performed following chest and sinus exacerbations, also varied widely between centres. Our survey revealed a great deal of variation across Europe in how frequently patients with PID visit the clinic and how frequently some monitoring tests are carried out. These results highlight the urgent need for consensus guidelines on how to monitor lung complications in PID patients. Abstract : To understand how patients with primary immunodeficiency (PID) and antibody deficiency are monitored, we conducted a survey of 13 PID centres across Europe. Our survey revealed a great deal of variation in how frequently patients with PID visit the clinic and how frequently some monitoring tests are carried out; for example, variation existed between centres in the frequency with which some laboratory monitoring tests are performed, including testing for IgG subclass levels and specific antibodies (see figure). Our results highlight the urgent need for consensus guidelines on how to monitor lung complications in PID patients.